Developing General Guidelines for Textbook Writing Process - Saxsena, Tanya (Voices of Teachers and Teacher Educators, 2018)
This article talks about Chhattisgarh mathematics textbook writing process for secondary grades. It investigates how the principles and framework of the textbook evolved and their alignment to the NCF-2005. This article begins with the development of common guidelines. Then it focuses how these guidelines are linked with the objective of learning of mathematics at the secondary stage and the content presented in the book. The implication of the principles is highlighted as National Curriculum Framework some of the chapters are added, types of problems, and in various other ways.